Informality, property rights, and poverty in China's "favelas". (February 2016) - Webster, Chris; Wu, Fulong; Zhang, Fangzhu; Sarkar, Chinmoy
Highlights: Studies relationships between informality, property rights (PR), and poverty in 3 Chinese cities. Draws upon entitlements theories of Sen, de Soto, Ostrom, Alchian, and Coase. Household performances on 6 poverty domains expressed as function of 4 PR domains. Some PR associated with lower poverty indicators- Sen effects and de Soto effects . Absence/weakness/ambiguity of PR reduces poverty indicators on some domains. Summary: In this study of households living in informal settlements in three principal Chinese cities, we analyze the associations between informality, property rights, and poverty. We propose that informality can be understood in terms of property rights (presence/absence, strength, completeness, and ambiguity). Drawing on the property rights (entitlements) theories of Sen, de Soto, Ostrom, Alchian, and Coase, we refine a list of property rights effects that can be tested empirically. Using a household questionnaire survey of 1, 208 respondents from a representative sample of 60 urban villages in Beijing, Shanghai, and Guangzhou, we use robust regression models to detect statistical relationships between household performance on six poverty domains as a function of four property rights domains, controlling for income, human capital, and other influences. We find evidence for what we call Sen effects and de Soto effects. Our models show that some property rights are associated with lower poverty indicators. But we also find evidence to show that the absence, weakness, or ambiguity of property rights also reduce poverty indicators on particular domains, through what we assume to be a substitution effect. Informal settlements permit poorer household to live at lower costs than is usually, or officially, acceptable, and thus spend more on other welfare-enhancing expenditures. The distribution of property rights determines the size, distribution, and impacts of these trade-offs and shapes the economic and social performance of informal settlements.